High Production of Cellulase and Xylanase in Solid-State Fermentation by Trichoderma reesei Using Spent Copra and Wheat Bran in Rotary Bioreactor - Teerin Chysirichote; Natthanon Phaiboonsilpa; Navadol Laosiripojana (Industrial & Engineering Chemistry Research, 2023)
The enzyme production for lignocellulose saccharification by solid-state fermentation (SSF) of a food manufacturing byproduct was successfully carried out in a 30 L rotary bioreactor. Defatted spent copra (SC) supplemented with wheat bran (WB) was used as a substrate for the SSF of Trichoderma reesei and aerated at various rates. Regression analysis showed that the carbohydrate/protein (C/P) ratio of the substrate and the supplied aeration rate were the important factors for producing the enzyme cocktail, including cellulases (FPase, CMCase, and cellobiase) and xylanase. The substrate containing SC:WB of 3:2 (or the C/P ratio of 5.4) and the aeration of 1.0 L kg–1substrate min–1 were found to enhance the production of the enzymes up to 5.68, 8.66, 29.2, and 34.44 U g–1 of dry substrate for FPase, CMCase, cellobiase, and xylanase activities, respectively. This discovery provided a promising environment for other substrates to produce multi-enzymes for lignocellulosic saccharification. Additionally, mathematical models were generated to predict the saccharifying degree of the produced enzyme for lignocellulose saccharification.
Keywords: Biofuel production and bioconversion; Microbial Metabolic Engineering and Bioproduction; Enzyme Catalysis and Immobilization